Interdisciplinary Blockchain Education: Utilizing Blockchain Technology From Various Perspectives - Düdder, Boris; Fomin, Vladislav; Gürpinar, Tan; Henke, Michael; Iqbal, Mubashar; Janavičienė, Viktorija; Matulevičius, Raimundas; Straub, Natalia; Wu, Haiqin (Frontiers in Blockchain, 2021)
The early development of blockchain technology (BCT) has already demonstrated the technology’s potential to serve the needs of different industries. BCT has also become established as a popular research topic in different scientific disciplines. This paper aims at introducing how several relevant scientific disciplines - supply chain management; management, economics and finance; computer science; security engineering - see the research and education perspectives for BCT. A field review is conducted to present challenges and opportunities of BCT, as well as suggestions for future research and education on the topic as seen from the selected differenct perspectives. The paper also presents methods for combining relevant disciplines in a modular online course to address the stated challenges and promote interdisciplinary blockchain education.